Standardization of Emergency Department Clinical Note Templates: A Retrospective Analysis across an Integrated Health System - Evans, Christopher S.; Bunn, Barry; Reeder, Timothy; Patterson, Leigh; Gertsch, Dustin; Medford, Richard J. (Applied Clinical Informatics, 2024)
Background and Objective Clinical documentation is essential for conveying medical decision-making, communication between providers and patients, and capturing quality, billing, and regulatory measures during emergency department (ED) visits. Growing evidence suggests the benefits of note template standardization; however, variations in documentation practices are common. The primary objective of this study is to measure the utilization and coding performance of a standardized ED note template implemented across a nine-hospital health system.Methods This was a retrospective study before and after the implementation of a standardized ED note template. A multi-disciplinary group consensus was built around standardized note elements, provider note workflows within the electronic health record (EHR), and how to incorporate newly required medical decision-making elements. The primary outcomes measured included the proportion of ED visits using standardized note templates, and the distribution of billing codes in the 6 months before and after implementation.Results In the preimplementation period, a total of six legacy ED note templates were being used across nine EDs, with the most used template accounting for approximately 36% of ED visits. Marked variations in documentation elements were noted across six legacy templates. After the implementation, 82% of ED visits system-wide used a single standardized note template. Following implementation, we observed a 1% increase in the proportion of ED visits coded as highest acuity and an unchanged proportion coded as second highest acuity.Conclusion We observed a greater than twofold increase in the use of a standardized ED note template across a nine-hospital health system in anticipation of the new 2023 coding guidelines. The development and utilization of a standardized note template format relied heavily on multi-disciplinary stakeholder engagement to inform design that worked for varied documentation practices within the EHR. After the implementation of a standardized note template, we observed better-than-anticipated coding performance.
Keywords: clinical documentation; electronic health record; note templates